Assessment of the efficacy of a feed additive consisting of ferrous lysinate sulfate for all animal species (Phytobiotics Futterzusatzstoffe GmbH). (11th January 2023) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of ferrous lysinate sulfate for all animal species. The safety of the additive for the target species, consumer, user and the environment has already been assessed previously, however the efficacy remained inconclusive due to limitations in the study with chickens for fattening. In the present assessment, the applicant submitted a new efficacy study in weaned piglets. After the assessment of the new data submitted by the applicant, the FEEDAP Panel could not conclude on the efficacy of ferrous lysinate sulfate in weaned piglets.